www.localgovernment.com: opening the window to on-line democracy. - Bowser, Brandi (American City & County, 1998)
Internet tools can be very useful for city and county governments. The most common online tool used is e-mail, which has the advantage of being able to alert users to the availability of data and services. Web sites allow governments to provide continuous access to information and interactive tools. Certain sites allow users to voice their opinions on official issues. Electronic commerce and video-conferencing can save government travel costs and time.